(untitled) (American Journal of Interdisciplinary Research and Development, 2026)
This article discusses the role of games in the development of preschool children, its types, and their impact on children. The game is the main activity of preschool children. Therefore, scientific conclusions have been made that it is appropriate for educators to organize training and other activities in the form of games.